A Child Who Suddenly Freezes While Trying to Cross Crosswalks-Unique Clinical Manifestation of Paroxysmal Kinesigenic Dyskinesia: A Case Report - Sae Yoon Kim; JiYoung Ahn; Soyoung Kwak; Min Cheol Chang (MDPI AG, 2020)
(1) Background: We report the case of a patient with a unique clinical presentation of inability to cross crosswalks due to paroxysmal kinesigenic dyskinesia (PKD). (2) Case presentation: A 14-year-old boy presented with the inability to move his right leg at gait initiation from the standing position. This episode lasted for approximately 20-30 s and manifested 1-3 times a day. The difficulty in gait initiation usually occurred when the patient tried to cross crosswalks when the traffic light turned from red to blue. His right arm stiffened occasionally while trying to write with a pencil and eat food with a spoon or chopsticks. Other neurological manifestations and pain were absent during these episodes. No neurological symptoms were observed between the attacks. Brain magnetic resonance imaging did not reveal any abnormalities. A next-generation sequencing study revealed a pathological variant in the proline-rich transmembrane protein 2 (PRRT2) gene. The patient was diagnosed with PKD. His symptoms disappeared completely after treatment with carbamazepine (100 mg/day). (3) Conclusions: The symptoms of PKD can be successfully controlled using antiepileptic medications. Therefore, clinicians should be aware of the clinical manifestations of PKD to provide appropriate treatment.